Circular economy needs the resilient systems in COVID-19 pandemic - Tseng, Ming-Lang; Ardaniah, Viqi; Bui, Tat-Dat; Mohd Helmi Ali,; Chiu, Anthony SF (Penerbit Universiti Kebangsaan Malaysia, 2020)
This note reveals the gaps from circular economy (CE) and resilience in the literature during COVID-19 pandemic. The disruptive event affects the circularity in the supply chain due to numerous single-use-products in food, health, plastic industries. The unsustainable production and consumption is harmful for social, ecological, and economic systems. The industrial practices need a highly resilient network to have better visibility and agility to shift sourcing. Prior studies reveal the gap that CE needs the resilient systems. Still, there is a need to conceptualize and models resilience in CE studies using quantitative and qualitative approaches.